Ultra-Brief Crisis IPT-A Based Intervention for Suicidal Children and Adolescents (IPT-A-SCI) Pilot Study Results - Haruvi Catalan, Liat; Levis Frenk, Mira; Adini Spigelman, Ella; Engelberg, Yair; Barzilay, Shira; Mufson, Laura; Apter, Alan; Benaroya Milshtein, Noa; Fennig, Silvana; Klomek, Anat Brunstein (Frontiers in Psychiatry, 2020)
In recent years, suicidal behaviors have shown substantial increase worldwide. This trend is also prominent in Israel and has led to a dramatic increase in mental health treatment demand resulting in long wait times and low treatment acceptance rate. To address the critical need in crisis intervention for children and adolescents at suicidal risk we developed an ultra-brief acute crisis intervention, based on Interpersonal Psychotherapy (IPT). IPT is an evidence-based intervention for various psychopathologies among different age groups. The current adaptation of IPT-A is comprised of five weekly sessions, followed by monthly follow-up caring email contacts to the patients and their parents, over a period of three months. This paper aims to review the theoretical foundation of this intervention, describe the research design, and present preliminary results of a pilot study. Preliminary Results from our samples of 26 adolescents indicate meaningful trends for both the suicidal ideation (SIQ) and depression (MFQ) outcome measures. Significant interaction was found concerning suicidal ideation but not for depression. Main limitations include small sample size and stratified controls. The treatment appears to be safe, feasible and acceptable and initial results show promising trends to support further study of the approach.